Population and subspecies diversity at mouse centromere satellites. - Arora, Uma P.; Charlebois, Caleigh.; Lawal, Raman Akinyanju.; Dumont, Beth L. (Tufts University. Tisch Library., 2021)
Keywords: Centromere, CENP-A, Inbred mice, Wild mice, Evolution, Bioinformatics, Satellite DNA, Genetic diversity, Mammalian genomics, k-mer.; Springer Open.